Numerical analysis of internal erosion impact on underground structures: Application to tunnel leakage. (September 2022) - Yang, Jie; Yin, Zhen-Yu; Laouafa, Farid; Hicher, Pierre-Yves
Abstract: Water leakage is one of the most critical factors that affect the ground movement and structural behaviour during and after the construction of the shield tunnel. Currently, very limited attention has been paid to the effect of the loss of fine particles induced by the water leakage, namely the internal erosion. In this study, the evolution of soil porosity, gradation, seepage flow and the induced ground movement and lining stress change due to tunnel leakage has been numerically investigated using a novel coupled hydro-mechanical approach formulated within the continuous porous medium framework. The detachment and transport of fines particles within the seepage flow are considered by a four-constituent model of internal erosion. The induced influence on the soil mechanical behaviour is modelled by a critical-state-based constitutive model considering the evolution of the fines content. Using the proposed approach, the time–space evolution of the eroded zone and the hydro-mechanical response in the cases of a single tunnel and two crossing tunnels are identified. The results indicate that the commonly used pore pressure reduction-based method without considering internal erosion will under-estimate the leakage induced lining stress change and ground movement. Moreover, the influence of three-dimensional conditions, hydraulic boundary conditions and tunnel characteristics are highlighted. Highlights: A hydro-mechanical approach of internal erosion around underground structures is formulated. The migration of fine particles and the induced mechanical influence are analysed. The erosion and pore pressure reduction induced responses due to tunnel leakage are demonstrated. The influence of the 3D condition and the boundary conditions are emphasized.